Digital Marketing Strategy Analysis in Increasing Sales Volume of Suweger Indonesia Brand in Surabaya - Yunida Anggun Saputri; Indah Respati Kusumasari (Universitas KH. Abdul Chalim Mojokerto, 2025)
This research aims to evaluate digital marketing strategies in increasing sales volume of the Suweger Indonesia brand in Surabaya. The research method used is descriptive qualitative through observation, interviews, and documentation. The results indicate that the utilization of social media (Instagram and TikTok), online delivery services, and creative content relevant to Gen Z significantly contribute to attracting consumers and boosting sales. The SWOT analysis shows a strength score of 1.93 and a weakness score of 0.39 (a difference of 1.54), as well as an opportunity score of 2.10 and a threat score of 0.86 (a difference of 1.24). The IFAS score of 2.32 and EFAS score of 2.96 place Suweger in Quadrant I, indicating an aggressive growth (SO) strategy as the appropriate approach. This strategy includes optimizing digital platforms, launching healthy menu options, collaborating with micro-influencers, and developing a digital reward system to strengthen customer loyalty.